Dynamic simulation of articulated soft robots - Weicheng Huang (Nature Portfolio, 2020)
To advance the design of soft robots, novel computational frameworks that accurately model the dynamics of soft material systems are required. Here, the authors report a numerical framework for studying locomotion in limbed soft robots that is based on the discrete elastic rods algorithm.